Pitch Angle Control of Wind Turbine Using Adaptive Fuzzy-PID Controller - A. Hamoodi, Safwan; I. Hameed, Farah; N. Hamoodi, Ali (EAI Endorsed Transactions on Energy Web, 2020)
The control strategy for wind turbine is very important an equipage that diverts the kinetic energy of the wind to electrical power. The rotation speed control of wind turbine is necessary for highest degree energy capture and pitch angle advanced control planning depending on traditional PID controller and fuzzy logic adaptive PID controller. Input variables of fuzzy logic controller (FLC) are selected to give smooth control of pitch angle which in turns will adjust the speed of wind turbine at reference level. A very small adaptation in pitch angle has influence on the ancestry of obtainable energy, torque and output power of the grid. A modeling of self-excitation induction generator (SEIG) 1KW wind turbine is achieved by Matlab/Simulink package and all modeling equations are studied. The effect of pitch angle on speed of the wind turbine is studied and a comparison between traditional PID controller and fuzzy logic adaptive PID controller was made.